2010
DOI: 10.1016/j.chieco.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child co-residence and bequest motives in China

Abstract: In this paper, I discuss the actual conditions and the determinants of co-residence between older parents and their children in China, especially the impact of bequest motives on parent-child co-residence, using micro data from the "Survey of Living Preferences and Satisfaction," conducted at Osaka University. More specifically, I use three subsamples of older respondents (those who live in urban areas, those who live in rural areas, and the pooled sample of both) to analyze the impact of bequest motives and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…On the one hand, we note that a scarce provision of basic public services and a less developed social security system imply that most elderly Chinese rely on their children for care and support, see Banerjee et al (2010). This is consistent with a traditional self-reliance within Chinese families (see e.g., Yin (2010)). Indeed, while the typical co-residence between parents and their son's family gradually becomes outdated in modern China, family ties are still tight.…”
Section: Introductionsupporting
confidence: 67%
“…On the one hand, we note that a scarce provision of basic public services and a less developed social security system imply that most elderly Chinese rely on their children for care and support, see Banerjee et al (2010). This is consistent with a traditional self-reliance within Chinese families (see e.g., Yin (2010)). Indeed, while the typical co-residence between parents and their son's family gradually becomes outdated in modern China, family ties are still tight.…”
Section: Introductionsupporting
confidence: 67%
“…Quantitative analysis for United States populations found no evidence of this effect, although a recent Chinese study did (Perozek, 1998;Yin, 2010).…”
Section: Developing a Conceptual Framework For Understanding Family Cmentioning
confidence: 91%
“…Instead of using realistic values of the child's income, we thus use residuals of the regression of the child's income on householder's age (proxy variable for tenure) and its squared value. Even considering these points, the empirical results are consistent with those in Table 4. 20 (Tomassini, Wolf, and Rosina, 2003;Angelini, 2007), the US (Bernheim, Shleifer, and Summers, 1985;Cox, 1987), and East Asian countries (Horioka, 2002;Yamada, 2006;Kureishi and Wakabayashi, 2009;Yin, 2010). However, there are usually cultural di¤erences in parents' (children's) attitudes toward children (parents) between countries.…”
Section: Discussionmentioning
confidence: 99%
“…The motive behind transfer decisions, however, is a controversial issue. Many studies in relation to intergenerational transfers or bequests have suggested parents are more likely to possess an exchange motive rather than an altruistic motive (Bernheim, Shleifer, and Summers, 1985;Cox, 1987;Horioka, 2002;Tomassini, Wolf, and Rosina, 2003;Yamada, 2006;Angelini, 2007;Kureishi and Wakabayashi, 2009;Yin, 2010). That is, parents tend to enter an agreement with their children whereby their adult children agree to provide a service in exchange for receiving gifts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation